Aptamer-siRNA chimera and gold nanoparticle modified collagen membrane for the treatment of malignant pleural effusion - Chen, Wen; Guo, Fengjie; Ren, Zhipeng; Wang, Linghui; Li, Tinghui; Hou, Xiaobin (Frontiers in Bioengineering and Biotechnology, 2022)
Malignant pleural effusion is one of the most common complications of advanced lung cancer and there is no effective clinical treatment at present. Here, we constructed an aptamer-siRNA chimeras/PEI/PEG/ gold nanoparticle (AuNP) /collagen membrane that can progressively activate T cells by layer by layer assembly. Electron microscope showed this collagen membrane could be divided into 10 layers with a total thickness of 50-80μm, and AuNPs could be observed. Aptamer-siRNA chimeras could bind specifically to OX40+ cells and silencing programmed death receptor-1 (PD-1) gene. In vitro experiments demonstrated that chimeras/PEI/PEG/AuNPs gradually activated T cells to continuously kill lung adenocarcinoma cells in malignant pleural effusion. Animal experiments showed that chimeras/PEI/PEG/AuNP/collagen membrane effectively treated malignant pleural effusion. Compared with PD-1 inhibitor group, the number of cancer cells, ki-67 proliferation index and CD44 expression in the pleural effusion was significantly decreased and the lymphocyte/cancer cell ratio was significantly increased in the chimeras/AuNP-CM group. Flow cytometry showed that compared with PD-1 inhibitor group, T cell number in the chimeras/AuNP-CM group was significantly increased, while the proportion of PD-1+ T cells was markedly decreased. In conclusion, we constructed an chimeras/PEI/PEG/AuNP/collagen membrane, which was more effective in the treatment of malignant pleural effusion, and had less side effects than PD-1 inhibitors.